Analysis of shot, unforced error, number of shot and duration of the match between Shi Yuqi and Lee Chong Wei in All England 2017 / Muhamad Fitri Adnan - Adnan, Muhamad Fitri (Faculty of Sport Science and Recreation, 2018)
This study was conducted in order to analysis of shot, unforced error, number Of shot and duration of the match between Shi Yuqi and Lee Chong Wei in All England 2017. Five match starts from quarter final to final match were selected to be observed. The indicator include for this analysis were the shot, unforced error, number of shot and duration of the match. Mann Whitney test used to see the significant of this study. For shot, first type of shot which is forehand Lee Chong Wei (Mean ± SD), (30.33±8.083) and Shi Yuqi forehand (17.67±11.7l9). Next, for backhand shot, based on the analysis for Lee Chong Wei (Mean± SD), (16.33±11.150) and Shi Yuqi (Mean ± SD), (14.33±6.658). For Lee Chong Wei drop is (Mean ± SD), (31.00±7.211) and Shi Yuqi drop (Mean ± SD), (52.67±34.962). Last for number of shot is jumping smash. Lee Chong Wei (Mean ± SD), (25.00±3.606) and Shi Yuqi (Mean ± SD), (24.33±.577). The second indicator is unforced error. Based on the results Lee Chong Wei out is (Mean ± SD), (6.33± 3.055) and Shi Yuqi out (9.67± 2.082). Next is Lee Chong Wei long (Mean ± SD), (.OO±.OOO) and Shi Yuqi long (Mean ± SD), (.OO±.OOO). For short and wrong court Lee Chong Wei and Shi Yuqi also same like long which is long (Mean ± SD), (.OO±.OOO). Lastly for unforced error is net. Lee Chong Wei is (Mean ± SD), (7.33±5.508) and Shi Yuqi (Mean ± SD), (8.67±4.04l). Next indicator is number of shot, Lee Chong Wei (Mean ± SD), (259.33±34.078) and Shi Yuqi (Mean ± SD), (2l5.67±75.745). Lastly indicator is duration of the match, Lee Chong Wei (Mean ± SD), (49.33±8.386) and Shi Yuqi (Mean ± SD), (43.33±7.024).